Tren Publikasi Ilmiah dalam Kajian Administrasi Publik: Analisis Bibliometric Data Scopus - Muhammad Ridwan Malik; Supriyadi Supriyadi; Syaparman Syaparman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Objective: This study aims to analyze the trend of scientific publications on Public Administration studies published in Scopus indexed journals based on 2014 to 2024. Methods: Data was obtained based on the Scopus database in October 04, 2024 at 21:30 WIB using the word “Public Administration” and found 19,743 document results that were used to search in several categories, including tittle, abstract and keywords. The author conducts content analysis using VOSviewer software version 1.6.17 which functions to visualize the interactions that occur in the research data obtained. The data collection process was carried out using analyze search in the document output. Meanwhile, data analysis is carried out based on infographic mapping of the development of research documents, mapping documents against data such as affiliation, country, subject area, type of publication which in the end sees the interaction of relationships that occur in research that studies Public Administration. Results: The study of public administration based on the 2014-2024 range conducted by several researchers continues to grow based on year to year seen in the infographic there are 19,743 published documents discussing Public Administration in various countries. The affiliation that actively conducts Public Administration studies is the research forum of the Russian Presidential Academy of National Economy and Public Administration, namely 161 documents conducted & the United States is the country that ranks first for scientific publications, namely 3,151 Scopus indexed documents.